Establishment method of metallurgical lime burning reduction model, establishment method of calcium-magnesium-silicon content model in metallurgical lime and application

By establishing a metallurgical lime burning reduction model and a calcium-magnesium silicon content model, combined with the melt sample weighing correction-X-ray fluorescence spectrometry, the problems of complex operation, long analysis cycle and serious matrix interference in the determination of metallurgical lime chemical composition are solved, and fast and accurate measurement results are achieved, which are suitable for large-scale daily production inspections.

CN119846002APending Publication Date: 2025-04-18PANGANG GRP PANZHIHUA STEEL & VANADIUM
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510029202.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, the chemical composition determination of metallurgical limes has problems such as complex operation, long analysis cycle, and serious matrix interference, which affects the accuracy and timeliness of the measurement results.

Method used

By establishing a metallurgical lime burning reduction model and a calcium-magnesium silicon content model, the melt sample weighing correction-X-ray fluorescence spectroscopy is used to reduce the measurement process and improve detection efficiency and accuracy.

Benefits of technology

It realizes the reduction of metallurgical lime burning and rapid and accurate determination of chemical components, shortens the detection cycle, from 4.5 hours to 2 hours, reduces the energy consumption of sample burning, and is suitable for large-scale daily production inspections.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005233660870000031
    Figure BDA0005233660870000031
  • Figure BDA0005233660870000032
    Figure BDA0005233660870000032
  • Figure BDA0005233660870000071
    Figure BDA0005233660870000071
Patent Text Reader

Abstract

The invention provides a method for establishing a metallurgical lime burning reduction model and a method for establishing a calcium-magnesium-silicon content model in metallurgical lime, and further provides application of the method for establishing the models. The establishment method of the model provided by the invention comprises the following steps: preparing a series of standard samples of which the ignition loss and the content of each component have a proper gradient range, directly melting and flaking, weighing the mass of the molten flaking, and carrying out fitting regression on the loss amount of the sample before and after melting and a standard ignition loss value, so as to establish an ignition loss correction model; after dilution ratio correction is carried out on the measured value of each component, iterative regression calculation is carried out on the measured value and the burning loss, and a basic effect correction model caused by the burning loss is established; therefore, a model for rapidly determining the burning loss of the metallurgical lime and the contents of chemical components such as calcium oxide, magnesium oxide and silicon dioxide by using the fuse piece weighing correction-X-ray fluorescence spectrometry is established, and accurate determination of the burning loss of the metallurgical lime and the contents of the calcium oxide, the magnesium oxide and the silicon dioxide can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of detection technology, and in particular to a method for establishing a metallurgical lime burning loss model, and a method for establishing a calcium, magnesium and silicon content model in metallurgical lime and applications thereof. Background Art

[0002] Metallurgical limes such as active lime, quicklime, passivated lime, high-magnesium lime, dolomite and limestone are fluxes for ironmaking and sintering and desulfurizers for steelmaking. Chemical compositions such as calcium oxide, magnesium oxide and silicon dioxide in metallurgical lime are important indicators for factory acceptance. Rapid and accurate determination of the chemical composition of metallurgical lime is crucial to the production, quality and cost of the smelting process.

[0003] The chemical composition of metallurgical lime is usually determined by chemical methods, which are cumbersome to operate and have a long analysis cycle, and cannot meet the needs of modern production process control. X-ray fluorescence spectrometry can be used to determine the chemical composition of metallurgical lime, which can achieve simultaneous determination of multiple elements. It has the characteristics of simple operation, high efficiency and environmental protection, and is widely used in the domestic metallurgical industry. In this process, tableting is used for sample preparation and X-ray fluorescence spectrometry is used for determination, but the matrix interference is serious and the accuracy of the determination results is poor; the melting method is used to prepare glassy samples, which eliminates the influence of mineral structure and particle size and improves the accuracy of metallurgical lime. This method generally adopts the two-step operation method of "ignition loss determination-melting tablet preparation" and uses the burning loss to correct the final result. However, the following problems were found in analytical practice: First, the two-step operation method requires more than 4.5 hours per batch of testing per week, which affects the timeliness of the report; second, the sample absorbs moisture and carbon dioxide in the air after burning, which affects the accuracy of the result. Summary of the invention

[0004] The technical problem solved by the present invention is to provide a method for establishing a metallurgical lime ignition loss model and a method for establishing a calcium, magnesium and silicon content model in metallurgical lime. The models established in the present application can accurately measure the metallurgical lime ignition loss and calcium, magnesium and silicon content respectively.

[0005] In view of this, the present application provides a method for establishing a metallurgical lime burning loss model, comprising the following steps:

[0006] S1) burning the metallurgical lime to be tested;

[0007] The calcined metallurgical lime sample to be tested, the mold release agent and the flux are melted at high temperature to prepare a sheet, and the sheet is weighed after cooling, which is recorded as m1; the mold release agent and the flux are melted to prepare a sheet to obtain a blank sheet, and the blank sheet is weighed after cooling, which is recorded as m0;

[0008] The X-ray spectrometry method is used to detect the metallurgical lime molten slice to be tested;

[0009] S2) selecting a series of standard samples of limestone and a series of standard samples of dolomite respectively, and batching the burned series standard samples and the unburned series standard samples according to a mass ratio; the contents of loss on ignition, calcium oxide, magnesium oxide and silicon dioxide of the batching have a gradient and include the measurement range of each component in the metallurgical lime to be measured, and the weight of the burned series standard samples is the same as the weight of the metallurgical lime to be measured;

[0010] The batched series of standard samples are melted and sheeted;

[0011] The X-ray fluorescence spectrometry was used to detect the series of standard sample melt slices respectively;

[0012] S3) respectively plotting the X-ray fluorescence intensity of the metallurgical lime molten sheet to be tested, the X-ray fluorescence intensity of the series of standard sample molten sheets and the calibration curve; according to the calibration curve, calibrating with the ignition loss of the high temperature ignition method, establishing the metallurgical lime ignition loss I shown in formula (I) g Model;

[0013] I g =99.00-99.64×(m0-m1) (Ⅰ).

[0014] The present application also provides a method for establishing a calcium, magnesium and silicon content model in metallurgical lime, comprising the following steps:

[0015] S1) burning the metallurgical lime to be tested;

[0016] The calcined metallurgical lime sample to be tested, the mold release agent and the flux are melted to prepare slices, and the slices are weighed after cooling, which is recorded as m1; the mold release agent and the flux are melted to prepare slices to obtain a blank sample, and the blank sample is weighed after cooling, which is recorded as m0;

[0017] The X-ray spectrometry method is used to detect the metallurgical lime molten slice to be tested;

[0018] S2) selecting a series of standard samples of limestone and a series of standard samples of dolomite respectively, and batching the burned series standard samples and the unburned series standard samples according to a mass ratio; the contents of the loss on ignition, calcium oxide, magnesium oxide and silicon dioxide of the batching have a gradient and include the measurement range of each component in the metallurgical lime to be measured;

[0019] The batched series of standard samples are melted and sheeted;

[0020] The X-ray fluorescence spectrometry was used to detect the series of standard sample melt slices respectively;

[0021] S3) According to the dilution ratio correction, the theoretical model of silicon dioxide and magnesium oxide is shown in formula (II);

[0022]

[0023] The calcium oxide measured value in the series of standard samples is corrected for dilution ratio according to formula (II), and then compared with the standard value. The difference is equal to the loss on burn I g Iterative regression calculations were performed on limestone and dolomite to obtain correction models, wherein the correction model for calcium oxide in dolomite and its calcined products is shown in formula (III), and the correction model for calcium oxide in limestone and its calcined products is shown in formula (IV);

[0024]

[0025] Among them, W x is the final analysis result after calibration of the tested component, %; X is the direct measurement value, %; m is the sample mass, g; m1 is the sample piece mass, g; m0 is the reagent blank piece mass, g; I g is the loss on burning of the sheet, %; Ig is the model described in claim 1.

[0026] Preferably, in step S1), the burning temperature is 1100-1150° C., and the burning time is 5-10 min.

[0027] Preferably, the melting temperature is 1100-1150° C., and the melting is performed twice, with the first melting time being 8-12 minutes and the second melting time being 4-6 minutes.

[0028] Preferably, in step S3), the calcination temperature of the calcination series standard sample is 800-1000°C; in step S1), the release agent is selected from lithium iodide, and the flux is selected from Li2B4O7.

[0029] Preferably, in the series of standard samples, the CaO content in the limestone is distributed in steps from 70 to 98 wt%, and the CaO content in the dolomite is distributed in steps from 50 to 70 wt%.

[0030] Preferably, in step S3), the ignition loss Ig of the metallurgical lime to be tested measured by the high temperature weighing method is as shown in formula (I'), and the ignition loss of the metallurgical lime to be tested measured by the melting weighing method and the high temperature weighing method is linearly regressed to obtain the model shown in formula (I');

[0031] I g =(1.0000+m0-m1)×100............(I').

[0032] Preferably, the mass ratio of the burned product to the unburned product is distributed in a stepwise manner from 9.8:0.2 to 3:7.

[0033] The present application also provides the application of the established method in determining the loss on ignition of metallurgical lime.

[0034] The present application also provides the application of the established method in determining the calcium, magnesium and silicon contents in metallurgical lime.

[0035] The present application provides a method for establishing a loss on ignition model for metallurgical lime, which comprises preparing a series of standard samples having a suitable gradient range for loss on ignition and the content of each component, directly melting and preparing films, weighing the mass of the fused films, performing fitting regression on the loss of metallurgical lime to be measured before and after melting and the loss on ignition values ​​of the series of standard samples, and establishing a correction model for loss on ignition; the present application also provides a method for establishing a calcium, magnesium and silicon content model in metallurgical lime, which comprises preparing a series of standard samples having a suitable gradient range for loss on ignition and the content of each component, directly melting and preparing films, weighing the mass of the fused films, performing iterative regression calculation on the measured values ​​of each component after correction, and establishing a correction model for the basic effect caused by loss on ignition, thereby establishing a model for rapid determination of the chemical component contents of calcium oxide, magnesium oxide and silicon dioxide in metallurgical lime by fused film weighing correction-X-ray fluorescence spectrometry. The model establishment method provided in the present application utilizes molten sample weighing calibration-X-ray fluorescence spectrometry to determine the loss on ignition and chemical composition of metallurgical lime. Through iterative regression of the measurement results of different varieties and different series of standard products with different loss on ignition, a correction model for each analytical component and the loss on ignition of molten film is established, which reduces the process of determining the loss on ignition and component content, and shortens the detection cycle from the original 4.5 hours to 2 hours, which is used for large-scale daily production inspection. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a regression correction curve diagram of the measurement results in the method for establishing the metallurgical lime burning loss model of the present invention;

[0037] Figure 2 It is a regression correction curve diagram of CaO results of dolomite and calcined products in the method for establishing the calcium-magnesium-silicon model in metallurgical lime of the present invention;

[0038] Figure 3 It is a regression correction curve diagram of limestone and calcined product CaO results in the method for establishing the calcium-magnesium-silicon model in metallurgical lime of the present invention. DETAILED DESCRIPTION

[0039] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0040] In order to solve the problems of long detection cycle and accuracy of the two-step operation method of "loss on ignition determination-melting film preparation" in X-ray fluorescence spectrometry and achieve the purpose of low-consumption, rapid and accurate determination, the present application provides a method for rapid determination of metallurgical lime loss on ignition and calcium, magnesium and silicon content by melt sample weighing correction-X-ray fluorescence spectrometry. It establishes a correction model for each analytical component and dilution ratio and loss on ignition of melt film preparation through iterative regression of the determination results of different varieties and different series of standard products of loss on ignition. The test results show that the determination results have good precision, and at the same time, it realizes accurate determination of chemical components such as calcium oxide, magnesium oxide and silicon dioxide in metallurgical lime, reduces the energy consumption of sample burning, and fully meets the requirements of large-scale daily production inspection. Specifically, the present application first provides a method for establishing a metallurgical lime loss on ignition model, comprising the following steps:

[0041] S1) burning the metallurgical lime to be tested;

[0042] The calcined metallurgical lime sample to be tested, the mold release agent and the flux are melted at high temperature to prepare a sheet, and the sheet is weighed after cooling, which is recorded as m1; the mold release agent and the flux are melted to prepare a sheet to obtain a blank sheet, and the blank sheet is weighed after cooling, which is recorded as m0;

[0043] The X-ray spectrometry method is used to detect the metallurgical lime molten slice to be tested;

[0044] S2) selecting a series of standard samples of limestone and a series of standard samples of dolomite respectively, and batching the burned series standard samples and the unburned series standard samples according to a mass ratio; the contents of loss on ignition, calcium oxide, magnesium oxide and silicon dioxide of the batching have a gradient and include the measurement range of each component in the metallurgical lime to be measured, and the weight of the burned series standard samples is the same as the weight of the metallurgical lime to be measured;

[0045] The batched series of standard samples are melted and sheeted;

[0046] The X-ray fluorescence spectrometry was used to detect the series of standard sample melt slices respectively;

[0047] S3) respectively plotting the X-ray fluorescence intensity of the metallurgical lime molten sheet to be tested, the X-ray fluorescence intensity of the series of standard sample molten sheets and the calibration curve; according to the calibration curve, calibrating with the ignition loss of the high temperature ignition method, establishing the metallurgical lime ignition loss I shown in formula (I) g Model;

[0048] I g =99.00-99.64×(m0-m1) (Ⅰ).

[0049] In the method for establishing the model of metallurgical lime burning reduction, the present application first burns the metallurgical lime to be tested, the burning temperature is 1100-1150°C, the burning time is 5-10 minutes, and then the metallurgical lime to be tested, the release agent and the flux are melted at high temperature to prepare slices, and weighed after cooling, which is recorded as m1. Specifically, the flux is selected from Li2B4O7, and the release agent is selected from lithium iodide; the melting temperature is 1100-1150°C, and the melting is carried out twice, the first melting time is 8-12 minutes, and the second melting time is 4-6 minutes, so as to ensure that the metallurgical lime to be tested can be fully melted. At the same time, the release agent and the flux are melted to prepare slices to obtain blank samples, and the blank samples are weighed after cooling, which is recorded as m0, and the blank samples are used as control samples.

[0050] Then, the weighed metallurgical lime to be tested is detected by X-ray spectroscopy; the specific method of the X-ray spectroscopy detection is a method well known to those skilled in the art, and this application does not impose any particular limitation on this.

[0051] The present application selects a series of standard samples of limestone and a series of standard samples of dolomite respectively, weighs the burned series standard samples after burning, and mixes the burned series standard samples and the non-burned series standard samples according to the mass ratio. The component contents of the series of standard samples of limestone and the series of standard samples of dolomite have a gradient and include a determination method for each component in the metallurgical lime to be tested. The content of the gradient is first determined based on the content range of each component in the actual sample, and then the content of each component must cover the content range of each component in the actual sample according to the calibration curve. The calibration curve is drawn for the standard sample or the prepared standard sample. The content gradient of each component is not a strict isotropic gradient, and is roughly evenly distributed within the determination range. Specifically, in the series of standard samples, the CaO content in limestone is distributed in steps from 70 to 98 wt%, and the CaO content in dolomite is distributed in steps from 50 to 70 wt%; more specifically, the CaO content in the limestone can be distributed in steps of 75%, 78%, 81%, 83%, 85%, 87%, 90%, 91%, 93%, 95%, 96%, which also includes MgO, SiO2, Al2O3, and the above components are also designed in a gradient according to the proportion of limestone raw materials; the CaO content in the dolomite can be distributed in steps of 52%, 55%, 56%, 60%, 62%, 65%, 68%, 70%, which also includes MgO, SiO2 and Al2O3, and the above components are also designed in a gradient according to the proportion of dolomite raw materials. The design of the above gradient content can establish a quantitative relationship between the content of each component and the X-ray intensity for the actual sample determination, and can ensure the accuracy of the analysis structure within the detection range.

[0052] Afterwards, the series of standard samples after mixing are melted to prepare films, and the molten films of the series of standard samples are respectively detected by X-ray fluorescence spectrometry.

[0053] After the above test results, the X-ray fluorescence intensity and calibration curve of the metallurgical lime to be tested and the series of standard samples are plotted respectively; according to the calibration curve, the metallurgical lime ignition loss I shown in formula (I) is established. g Model;

[0054] I g =99.00-99.64×(m0-m1) (Ⅰ).

[0055] According to the theory, the sample weight loss on ignition I g The calculation should be model (Ⅰ'), but the experiment found that the ignition loss calculated by the molten sheet weighing method was higher than that of the high-temperature burning method. In order to be consistent with the high-temperature burning method, the molten sheet weighing calculation value and the ignition loss determined by the high-temperature burning method of model (Ⅰ") were linearly regressed to obtain the correction equation, as shown in the figure: Figure 1 As shown, after correction, the model described in formula (I) is obtained;

[0056] I g =(1.0000+m0-m1)×100............(I').

[0057] The above-mentioned high temperature burning method is specifically as follows: weigh mg of metallurgical lime to be tested in a crucible and weigh it, which is recorded as m a And then burn it at high temperature, cool it to constant weight and weigh it, record it as m b , calculate the loss on ignition according to formula (Ⅰ”);

[0058]

[0059] The present application also provides a method for establishing a calcium, magnesium and silicon content model in metallurgical lime, comprising the following steps:

[0060] S1) burning the metallurgical lime to be tested;

[0061] The calcined metallurgical lime sample to be tested, the mold release agent and the flux are melted to prepare slices, and the slices are weighed after cooling, which is recorded as m1; the mold release agent and the flux are melted to prepare slices to obtain a blank sample, and the blank sample is weighed after cooling, which is recorded as m0;

[0062] The X-ray spectrometry method is used to detect the metallurgical lime molten slice to be tested;

[0063] S2) selecting a series of standard samples of limestone and a series of standard samples of dolomite respectively, and batching the burned series standard samples and the unburned series standard samples according to a mass ratio; the contents of the loss on ignition, calcium oxide, magnesium oxide and silicon dioxide of the batching have a gradient and include the measurement range of each component in the metallurgical lime to be measured;

[0064] The batched series of standard samples are melted and sheeted;

[0065] The X-ray fluorescence spectrometry was used to detect the series of standard sample melt slices respectively;

[0066] S3) According to the dilution ratio correction, the theoretical model of silicon dioxide and magnesium oxide is shown in formula (II);

[0067]

[0068] The calcium oxide measured value in the series of standard samples is corrected for dilution ratio according to formula (II), and then compared with the standard value. The difference is equal to the loss on burn I g Iterative regression calculations were performed on limestone and dolomite to obtain correction models, wherein the correction model for calcium oxide in dolomite and its calcined products is shown in formula (III), and the correction model for calcium oxide in limestone and its calcined products is shown in formula (IV);

[0069]

[0070] Among them, W x is the final analysis result after calibration of the tested component, %; X is the direct measurement value, %; m is the sample mass, g; m1 is the sample piece mass, g; m0 is the reagent blank piece mass, g; I g is the loss on burning of the sheet, %; Ig is the model described in claim 1.

[0071] In the method for establishing a model for the calcium, magnesium and silicon contents in metallurgical lime, the above step 1) is the same as the method for establishing a model for the loss on ignition of metallurgical lime, and will not be described in detail here.

[0072] The present application then selects a series of standard samples of limestone and a series of standard samples of dolomite, and mixes the burned products and unburned products according to the mass ratio; the loss on burning, calcium oxide, magnesium oxide and silicon dioxide contents of the mix have a gradient and include the measurement range of each component in metallurgical lime; the mass ratio of the burned products and unburned products is distributed in a step-by-step manner from 9.8:0.2 to 3:7, specifically, the mass ratio of the burned products and unburned products can be 9.5:0.5, 9:1, 8.5:1.5, 8:2, 7.5:2.5, 7:3, 6.5:3.5, 6:4, 5:5, 4.5:5.5, 4:6, 3.5:6.5, 3:7 and the like. The contents of calcium oxide, magnesium oxide and silicon dioxide in the ingredients have a gradient and include the measurement range of each component in metallurgical lime. Specifically, in the series of standard samples, the content of CaO in limestone is distributed in steps from 70 to 98wt%, and the content of CaO in dolomite is distributed in steps from 50 to 70wt%; more specifically, the content of CaO in the limestone can be distributed in steps of 75%, 78%, 81%, 83%, 85%, 87%, 90%, 91%, 93%, 95%, and 96%, which also include MgO, SiO2, and Al2O3, and the above components are also designed in a gradient according to the proportion of limestone raw materials; the content of CaO in the dolomite can be distributed in steps of 52%, 55%, 56%, 60%, 62%, 65%, 68%, and 70%, which also include MgO, SiO2 and Al2O3, and the above components are also designed in a gradient according to the proportion of dolomite raw materials. The above-mentioned gradient content design can establish a quantitative relationship between the content of each component and the X-ray intensity for actual sample determination, and can ensure the accuracy of the analysis structure within the detection range.

[0073] The present application then melts the series of standard samples after batching, and the melting method is carried out according to the above description, which is not described in detail in the present application. X-ray fluorescence spectroscopy is then used to detect the series of burned standard samples after melting, and the detection method of X-ray fluorescence spectroscopy is carried out according to a method well known to those skilled in the art, and is not particularly limited in the present application.

[0074] The present application is then corrected according to the dilution ratio, and the theoretical model of silicon dioxide and magnesium oxide is shown in formula (II);

[0075]

[0076] The above-mentioned dilution ratio specifically refers to the proportion of the sample amount in the melted glass sheet in the entire glass sheet. In this application, due to the different burning losses of samples and inconsistent weight loss during the melting process, the relative content of each component has undergone different changes and must be corrected according to the uniform total mass of the melt.

[0077] Through verification, it is found that the above model is consistent with the actual results for silicon dioxide, magnesium oxide and aluminum oxide. Therefore, the above model can be used to determine the content of silicon dioxide and magnesium oxide in metallurgical lime.

[0078] After the calcium oxide content in metallurgical lime is corrected by the dilution ratio theoretical formula, the result has a large error with the standard value, because the burning loss of glass pieces is different, the matrix of the sample pieces is inconsistent, there are different matrix effects when performing X-ray fluorescence measurement, and the degree of influence of different varieties and high and low burning loss is different; the theoretical α coefficient calculated by instrument software iteration and fitting still has a large deviation. Through the derivation of experimental control data, the following corresponding variety component result correction model is obtained:

[0079]

[0080] According to the present invention, the measured values ​​of calcium oxide in the series of standard samples are corrected for dilution ratio according to formula (II) and then compared with the standard value. The error d gradually increases with the increase of the ignition loss Ig. Therefore, the error d is compared with the ignition loss Ig. g According to the iterative regression calculation of limestone and dolomite, the correction formula of error d is obtained, as follows: Figure 2 , Figure 3 As shown, it is substituted into the above correction model to obtain the following final calculation formula of calcium oxide, wherein the correction model of calcium oxide in dolomite and its calcined products is shown in formula (III), and the correction model of calcium oxide in limestone and its calcined products is shown in formula (IV);

[0081]

[0082] Among them, W x is the final analysis result after calibration of the tested component, %; X is the direct measurement value, %; m is the sample mass, g; m1 is the sample piece mass, g; m0 is the reagent blank piece mass, g; I g is the loss on burning of the sheet, %; Ig is the model described in claim 1.

[0083] Compared with the traditional chemical method, which has complicated operation, long analysis cycle and is not suitable for the needs of modern production process control, the model establishment method provided by the present application is faster and simpler; compared with the serious matrix interference and poor accuracy of the measurement result of the tableting sample preparation-X-ray fluorescence spectrometry, the molten matrix interference of the present invention is small and the detection accuracy is high; the two-step operation method of "loss on ignition determination-molten tableting" is adopted to reduce the loss on ignition determination process, without affecting the timeliness of the report, and at the same time avoid the absorption of moisture and carbon dioxide in the air after ignition, which affects the accuracy of the results; the present invention uses a method for determining the chemical composition of metallurgical lime by weighing and correcting the molten sample-X-ray fluorescence spectrometry, and iterates and regresses the measurement results of different varieties and different series of standard products of loss on ignition, and establishes a correction model for each analysis component and the dilution ratio and the loss on ignition of the melt tableting. This model is the first of its kind.

[0084] The present invention is suitable for the determination of loss on ignition and calcium, magnesium and silicon contents in metallurgical limes such as active lime, quicklime, passivated lime, high-magnesium lime, dolomite and limestone. Through iterative regression of the determination results of different varieties and different series of standard products of loss on ignition, a correction model of each analysis component, dilution ratio and loss on ignition of fusion film is established, the determination process of loss on ignition is reduced, and the detection cycle is shortened from the original 4.5 hours to 2 hours, thereby achieving accurate determination and reducing the energy consumption of sample ignition, and the invention can be used for large-scale daily production inspection.

[0085] In order to further understand the present invention, the method for establishing the metallurgical lime burning loss model, the method for establishing the calcium, magnesium and silicon content model in metallurgical lime and their applications are described in detail below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0086] Example

[0087] 1 Experimental methods

[0088] 1.1 Preparation of molten samples

[0089] 1.1.1 Sample melting and film preparation

[0090] Weigh 1g±0.1mg of the unburned product, place it in a platinum crucible, burn it at 1120℃±20℃ for 5min, take it out, add 6.0000g Li2B4O7, add 200g / L 0.5mL lithium iodide demoulding agent; melt it at 1120℃±20℃ for 10min, take it out, expose the bottom of the crucible and rotate it to remove all bubbles, shake it well, melt it again for 5min, take it out, expose the bottom of the crucible and rotate it to remove all bubbles, shake it well, let it stand horizontally and cool, pour the molten piece on a clean filter paper, weigh it after cooling, and record it as m1;

[0091] Melt a blank piece (without Li2B4O7 and lithium iodide) together with the test piece, weigh it after cooling, and record it as m0;

[0092] 1.1.2 Melting of calibration curve series standards

[0093] Select limestone and dolomite series standards, the content of each component has a certain gradient and covers the measurement range shown in Table 1; weigh 2.000g of the product into a 30mL porcelain crucible that has been pre-burned to constant weight, place it in a 980±10℃ muffle furnace, open the furnace door 3mm~5mm, and burn to constant weight; weigh 1g±0.1mg of the burned product, and melt and prepare slices according to 1.1.1;

[0094] 1.1.3 Melting of a series of standard samples for calibration model

[0095] Select limestone and dolomite standards, and prepare the burned and unburned products into a series of standard products with different burning loss according to a certain proportion, and melt the pieces according to the test melting piece method; see Table 2;

[0096] Table 1 Series of standards for calibration curve (wt%)

[0097] Label No. CaO MgO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> Ignition coefficient Limestone 11 77.24 14.24 5.83 0.57 0.5835 Limestone 7 81.35 13.61 2.57 0.50 0.5674 Limestone 5 90.16 5.52 2.35 0.59 0.5747 Limestone 3 96.47 0.74 1.37 0.38 0.5690 Dolomite07217a 60.46 38.35 0.040 0.032 0.5311 Dolomite07216a 65.24 33.31 0.091 0.045 0.5368 Dolomite 0119-2Wa 69.46 28.42 0.462 0.203 0.5412 Dolomite 10-113 56.21 37.82 3.870 0.371 0.5478

[0098] Table 2 Series of standard samples used for calibration model (wt%)

[0099] Serial number Standard CaO MgO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> Ignition coefficient 1 Limestone 5 51.78 3.17 1.35 0.34 42.53 2 <![CDATA[Limestone 3(9.5 灼烧 : 0.5)]]> 94.39 0.72 1.34 0.37 2.16 3 <![CDATA[Limestone 3(9 灼烧 : 1)]]> 92.31 0.71 1.31 0.36 4.31 4 <![CDATA[Limestone 3(8 灼烧 : 2)]]> 88.15 0.67 1.25 0.35 8.62 5 <![CDATA[Limestone 3(7 灼烧 : 3)]]> 84.00 0.64 1.19 0.33 12.93 6 <![CDATA[Limestone 3(5 灼烧 : 5)]]> 75.68 0.58 1.07 0.30 21.55 7 <![CDATA[Limestone 3(3 灼烧 : 7)]]> 67.37 0.52 0.96 0.26 30.17 8 Dolomite 10-113 30.79 20.72 2.120 0.203 45.22 9 <![CDATA[Dolomite 07217a(9.5 灼烧 :0.05)]]> 59.04 37.46 0.04 0.03 2.34 10 <![CDATA[Dolomite 07217a(9 灼烧 :1)]]> 53.66 36.11 3.70 0.35 4.52 11 <![CDATA[Dolomite 07216a(8 灼烧 :2)]]> 51.12 34.40 3.52 0.34 9.04 12 <![CDATA[Limestone 3(7 灼烧 :3)]]> 48.58 32.69 3.35 0.32 13.57 13 <![CDATA[Limestone 3(5 灼烧 :5)]]> 43.50 29.27 3.00 0.29 22.61 14 <![CDATA[Limestone 3(3 灼烧 :7)]]> 38.41 25.85 2.65 0.25 31.65

[0100] 1.2 Measurement

[0101] 1.2.1 Measurement conditions Prepare the X-ray spectrometer to normal working state and select the instrument measurement conditions, see Table 3.

[0102] Table 3 Recommended measurement conditions for S8 Tiger X-ray fluorescence spectrometer

[0103] element Analysis Line Light tube voltage, KV Phototube current, mA Measurement time, s Si Ka1 40 50 10 Ca Ka1 40 50 10 Mg Ka1 40 50 10 Al Ka1 40 50 10

[0104] Note: When using other instruments, the crystals and corresponding technical parameters provided by the manufacturer can be used.

[0105] 1.2.2 Preparation of calibration curve

[0106] Under the selected measurement conditions, measure the X-ray fluorescence intensity of the molten sheets of a series of standard products, and draw a calibration curve of X-ray fluorescence intensity and component content (after burning);

[0107] 1.2.3 Series of standard samples for measuring and calibrating the model

[0108] Measure a series of standard molten sheets, read the measured values ​​from the instrument, correct the dilution ratio, and iteratively regress with the loss on ignition to establish the correction model for each component;

[0109] 1.2.4 Test specimens

[0110] The sample melt is measured and the analysis result is obtained after correction.

[0111] 2 Results and discussion

[0112] 2.1 Sample burning loss correction model

[0113] According to the theory, the sample weight loss on ignition I g The calculation should be model (1), but the experiment found that the loss on ignition calculated by the melt weighing method is higher than that of the high-temperature ignition method system, see Table 4;

[0114] I g =(1.0000+m0-m1)×100………………(1);

[0115] In order to be consistent with the high temperature burning method, the calculated value of the melt weighing and the ignition loss determined by the high temperature burning method were linearly regressed to obtain the correction equation (such as Figure 1 ), substitute into formula (1), and obtain the final analysis result calculation model (2);

[0116] I g =99.00-99.64×(m1-m0)……………………(2);

[0117] Table 4 Results of loss on ignition determined by the burning method and the sample weighing method w%

[0118]

[0119]

[0120] 2.2 Calibration model for analysis results of each component

[0121] According to the experimental method, the powder is tried to be made into a glass-like molten sheet, the mass of the molten sheet is weighed, and the ignition loss is calculated based on the loss of the sample before and after melting; the calibration model series standard products are measured on an X-ray fluorescence instrument, and the measured values ​​are corrected for the dilution ratio and the matrix effect caused by the ignition loss. The measured values ​​of each analytical component in the sample are multiplied by the corresponding correction formula to obtain the analysis results of each component;

[0122] 2.2.1 Silicon, magnesium and aluminum test result correction model

[0123] According to the theory, the chemical composition correction model should be formula (3). Through experimental verification, the results of silicon dioxide, magnesium oxide, and aluminum oxide using the theoretical model (3) are consistent;

[0124]

[0125] Where: W xis the final analysis result after correction of the component to be tested, %; X is the direct measurement value, %; m is the sample mass, g; m1 is the sample mass, g; m0 is the reagent blank mass, g.

[0126] 2.2.2 CaO determination result correction model

[0127] After the calcium oxide content in metallurgical lime is corrected by the dilution ratio theoretical formula, the result has a large error with the standard value, because the burning loss of glass pieces is different, the matrix of the sample pieces is inconsistent, there is a different matrix effect when performing X-ray fluorescence measurement, and the influence of different varieties and high and low burning loss is different; the theoretical α coefficient calculated by instrument software iteration and fitting still has a large deviation; the correction model of the corresponding variety component result is obtained by deducing the experimental control data;

[0128]

[0129] Where: W x is the final analysis result after calibration of the tested component, %; X is the direct measurement value, %; m is the sample mass, g; m1 is the sample piece mass, g; m0 is the reagent blank piece mass, g; I g is the ignition loss of the tablet, %; a, b, c are the calcined product and the ignition loss, respectively. g Coefficients of the quadratic, linear, and constant terms of iterative regression.

[0130] According to the experimental method, the calcium oxide in the calibration model series standard samples in Table 4 was prepared, and the measured value was corrected for the dilution ratio according to formula (3), and then compared with the standard value (see Table 5). The error d gradually increased with the increase of the ignition loss Ig. Therefore, the error d and the ignition loss Ig were iteratively regressed for limestone and dolomite, and the correction formula for the error d was obtained, see Figure 2 , Figure 3 , Substituting the regression equation into formula (4), the final calculation formula of calcium oxide is obtained;

[0131] Final calculation formula for calcium oxide in dolomite and its calcined products (5).

[0132]

[0133] Final calculation formula for calcium oxide in limestone and its calcined products (6);

[0134]

[0135] Table 5 Matrix effect of loss on ignition on calcium oxide content determination w%

[0136]

[0137] 2.2.3 Model Application

[0138] Select 13 lime samples and measure them according to this method. Copy or enter the measured values ​​and sample weights into a spreadsheet, enter the calculation formulas for each component in the calibration result column, and pull down to automatically calculate the analysis results, see Table 6;

[0139] Table 6 Effect of ignition loss on CaO matrix effect (wt%)

[0140]

[0141] 2.2.4 Precision and accuracy of the method

[0142] Eight limestone standard samples were selected and independently measured five times according to this operation method. The test results are shown in Table 7. The results show that the range of the five measurements of silicon dioxide and magnesium oxide is within 0.11%, and the range of the five measurements of calcium oxide is within 0.30%, indicating that the precision of this method is good; the measurement results of this method are consistent with the certified values, indicating that the measurement results of this method are accurate and reliable;

[0143] Table 7 Precision and trueness test results (n = 5) w%

[0144]

[0145] 2.2.5 Method comparison

[0146] Thirteen lime and 14 high-magnesium lime samples were selected, and the contents of calcium oxide, magnesium oxide and silicon dioxide in the samples were determined by this method and the national standard method GB / T 3286.11-2022, respectively. The test results are shown in Table 8. The results show that the absolute values ​​of the deviations of the two methods for determining calcium oxide, magnesium oxide and silicon dioxide are within 0.42%, 0.28% and 0.13%, respectively, indicating that the results of the two methods for determining the contents of calcium, magnesium and silicon in metallurgical lime are consistent.

[0147] Table 8 Method comparison test results w%

[0148]

[0149]

[0150] 3 Conclusion

[0151] The post-ignition melt weighing correction method replaces the traditional loss on ignition correction method, thereby reducing the sample loss on ignition determination process, improving work efficiency, shortening analysis time, and reducing sample ignition energy consumption, which has good promotion and application value.

[0152] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0153] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for establishing a metallurgical lime burning loss model comprises the following steps: S1) burning the metallurgical lime to be tested; The calcined metallurgical lime sample to be tested, the mold release agent and the flux are melted at high temperature to prepare a sheet, and the sheet is weighed after cooling, which is recorded as m1; the mold release agent and the flux are melted to prepare a sheet to obtain a blank sheet, and the blank sheet is weighed after cooling, which is recorded as m0; The metallurgical lime molten slice to be tested is detected by X-ray spectroscopy; S2) selecting a series of standard samples of limestone and a series of standard samples of dolomite respectively, and batching the burned series standard samples and the unburned series standard samples according to a mass ratio; the contents of loss on ignition, calcium oxide, magnesium oxide and silicon dioxide of the batching have a gradient and include the measurement range of each component in the metallurgical lime to be measured, and the weight of the burned series standard samples is the same as the weight of the metallurgical lime to be measured; The batched series of standard samples are melted and sheeted; The X-ray fluorescence spectrometry was used to detect the series of standard sample melt slices respectively; S3) respectively plotting the X-ray fluorescence intensity of the metallurgical lime molten sheet to be tested, the X-ray fluorescence intensity of the series of standard sample molten sheets and the calibration curve; according to the calibration curve, calibrating with the ignition loss of the high temperature ignition method, establishing the metallurgical lime ignition loss I shown in formula (I) g Model; I g =99.00-99.64×(m0-m1) (Ⅰ)。 2. A method for establishing a calcium, magnesium and silicon content model in metallurgical lime, comprising the following steps: S1) burning the metallurgical lime to be tested; The calcined metallurgical lime sample to be tested, the mold release agent and the flux are melted to prepare slices, and the slices are weighed after cooling, which is recorded as m1; the mold release agent and the flux are melted to prepare slices to obtain a blank sample, and the blank sample is weighed after cooling, which is recorded as m0; The metallurgical lime molten slice to be tested is detected by X-ray spectroscopy; S2) selecting a series of standard samples of limestone and a series of standard samples of dolomite respectively, and batching the burned series standard samples and the unburned series standard samples according to a mass ratio; the contents of the loss on ignition, calcium oxide, magnesium oxide and silicon dioxide of the batching have a gradient and include the measurement range of each component in the metallurgical lime to be measured; The batched series of standard samples are melted and sheeted; X-ray fluorescence spectrometry was used to detect the series of standard sample molten slices respectively; S3) According to the dilution ratio correction, the theoretical model of silicon dioxide and magnesium oxide is shown in formula (II); The calcium oxide measured value in the series of standard samples is corrected for dilution ratio according to formula (II), and then compared with the standard value. The difference is equal to the loss on burn I g Iterative regression calculations were performed on limestone and dolomite to obtain correction models, wherein the correction model for calcium oxide in dolomite and its calcined products is shown in formula (III), and the correction model for calcium oxide in limestone and its calcined products is shown in formula (IV); Among them, W x is the final analysis result after calibration of the tested component, %; X is the direct measurement value, %; m is the sample mass, g; m1 is the sample piece mass, g; m0 is the reagent blank piece mass, g; I g is the loss on burning of the sheet, %; Ig is the model described in claim 1.

3. The establishment method according to claim 1 or 2, characterized in that: In step S1), the burning temperature is 1100-1150° C., and the burning time is 5-10 minutes.

4. The establishment method according to claim 1 or 2, characterized in that: The melting temperature is 1100-1150° C., and the melting is performed twice, with the first melting time being 8-12 minutes and the second melting time being 4-6 minutes.

5. The establishment method according to claim 1 or 2, characterized in that: In step S3), the calcination temperature of the calcination series standard samples is 800-1000°C; in step S1), the release agent is selected from lithium iodide, and the flux is selected from Li2B4O7.

6. The establishment method according to claim 1 or 2, characterized in that: In the series of standard samples, the CaO content in the limestone is distributed in steps from 70 to 98 wt%, and the CaO content in the dolomite is distributed in steps from 50 to 70 wt%.

7. The establishment method according to claim 1, characterized in that: In step S3), the ignition loss Ig of the metallurgical lime to be tested measured by the high temperature weighing method is as shown in formula (I'), and the ignition loss of the metallurgical lime to be tested measured by the melting weighing method and the high temperature weighing method is linearly regressed to obtain the model shown in formula (I'); I g =(1.0000+m0-m1)×100…………………(Ⅰ’)。 8. The establishment method according to claim 2, characterized in that: The mass ratio of the burned product to the unburned product is distributed in a stepwise manner from 9.8:0.2 to 3:

7.

9. Use of the method according to any one of claims 1, 3 to 7 in determining the loss on ignition of metallurgical lime.

10. Use of the method according to any one of claims 2, 3 to 6, and 8 in determining the calcium, magnesium, and silicon contents in metallurgical lime.

Citation Information

Cited By

  • Method for measuring calcium, silicon and magnesium in quick lime by X-ray fluorescence with ignition loss correction

    CN120142350A